Efficient Generation of Cardiac Purkinje‐like Cells from Embryonic Stem Cells by Activating cAMP Signaling. (2nd February 2017) - Tsai, Su‐Yi; Chen, Shuibing; Evans, Todd
Abstract: Strategies to derive cardiac conduction system (CCS) cells including Purkinje cells (PC) would facilitate models for mechanistic studies and drug discovery, and also provide new cellular materials for regenerative therapies. However, using current cardiac differentiation protocols, the differentiation efficiency of CCS cells is extremely low, typically below 1% of the culture. High‐throughput chemical screening is a powerful strategy for identifying small molecules that can activate signaling pathways to enhance embryonic stem cell (ESC) differentiation. We describe how to carry out a high‐ throughput screen to identify small molecules that can efficiently promote CCS generation from mouse ESCs. We also describe several assays, including immunofluorescence staining, electrophysiology, FACS analysis and quantitative real‐ time PCR, to characterize the phenotype of ESC‐derived PC. In summary, we describe an efficient way to identify small molecules that enhance cardiac PC generation. These protocols can be adapted to identify other rare cell lineages by directed differentiation from ESCs. © 2017 by John Wiley & Sons, Inc.